2023
DOI: 10.3389/fimmu.2023.1007624
|View full text |Cite
|
Sign up to set email alerts
|

Potential diagnostic markers and therapeutic targets for rheumatoid arthritis with comorbid depression based on bioinformatics analysis

Abstract: BackgroundRheumatoid arthritis (RA) and depression are prevalent diseases that have a negative impact on the quality of life and place a significant economic burden on society. There is increasing evidence that the two diseases are closely related, which could make the disease outcomes worse. In this study, we aimed to identify diagnostic markers and analyzed the therapeutic potential of key genes.MethodsWe assessed the differentially expressed genes (DEGs) specific for RA and Major depressive disorder (MDD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Uniform manifold approximation and projection (UMAP) analysis was performed to assess homogeneity, repeatability, and differences between the groups. Samples selected with a median that is basically on the same horizontal line for subsequent analysis ( Nayan et al, 2023 ; Zhou et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uniform manifold approximation and projection (UMAP) analysis was performed to assess homogeneity, repeatability, and differences between the groups. Samples selected with a median that is basically on the same horizontal line for subsequent analysis ( Nayan et al, 2023 ; Zhou et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gene Ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed, and a protein–protein interaction network (Genomes) was constructed. The MCODE plugin, CytoHubba plug-in, and CytoNCA algorithms were used to identify key genes related to AD and comorbid PD ( Nayan et al, 2023 ; Zhou et al, 2023 ). A connectivity map (CMap) was generated to identify the optimal drug for treating AD and comorbid PD.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) and depression are prevalent diseases that harm patient quality of life and impose a significant economic burden on society ( 28 , 29 ). Depression is a frequent comorbidity in patients with RA, which not only reduces treatment effectiveness but also increases the risk of disability and death ( 30 ).…”
Section: Overview Of the Connection Between Gut Microbiota And Depres...mentioning
confidence: 99%
“…Some potential biomarkers associated with depression in RA are IL-6, CRP, fibrinogen and SAA, although the majority of these markers mainly reflect inflammation, which may not be specific enough to help in the decision of treatment choices. A recent work using bioinformatic analysis and machine learning-based methods identified several genes likely involved in the mechanism underlying RA with depression, and also indicated that RA combined with depression is related to six diagnostic markers ( AURKA , BTN3A2 , CXCL10 , ERAP2 , MARCO , PLA2G7 ) [ 6 ], which could represent candidate biomarkers but need to be validated in RA cohorts. Treatment of RA-associated depression seems to be different from other forms.…”
mentioning
confidence: 99%
“…In RA patients both tocilizumab and infliximab decrease depressive symptoms, but their effect on depression without RA is not evident [ 7 ]. Vice versa, in cases of depression in RA, antidepressants do not seem to be highly effective [ 6 ]. For depression in RA, many studies have shown beneficial effect of non-pharmacological treatments, for example there is some data regarding the efficacy of mind–body therapies like meditation, mindfulness or yoga [ 8 ].…”
mentioning
confidence: 99%